Application of vibration-isolating supports with elastic rubber elements to decrease the risk of pipeline vibration - Кіпоренко, Ганна Сергіївна; Поліщук, Сергій Михайлович (Eastern-European Journal of Enterprise Technologies, 2012)
The target of the research is to explain the application of vibration-isolating damping supports with elastic rubber element to decrease the risk of pipeline vibrations, which can occur during transportation of heat-transfer agent (water, steam, water-steam mixture). The application of the supports is proved by the essential advantages in comparison with the existing manner of fastening of the pipeline, namely the possibility of application of support on the vertical as well as horizontal areas, the regulation of rigidity of fastening element, the simplicity of construction. Given supports may be applied at nuclear power station, thermal power station as well as at the other facilities using industrial pipelines. As an example, the article suggests the data of gain-frequency characteristics of pipeline area before and after the installation of the support. The results show the decrease of vibration amplitude by an order of magnitude after the installation of supports that prove their efficiency.